Buckling and postbuckling of CNT-reinforced composite sandwich cylindrical panels subjected to axial compression in thermal environments - Tung, Hoang Van; Long, Vu Thanh (Vietnam Journal of Mechanics, 2019)
An analytical investigation on the buckling and postbuckling behavior of carbon nanotube reinforced composite (CNTRC) sandwich cylindrical panels exposed to thermal environments and subjected to uniform axial compression is presented in this paper. Beside sandwich model with CNTRC face sheets in the literature, the present work suggests a sandwich model with CNTRC core layer and homogeneous face sheets. Carbon nanotubes (CNTs) are reinforced into matrix phase through uniform or functionally graded distributions. Effective properties of nanocomposite layers are determined according to extended rule of mixture. Formulations are based on the first order shear deformation theory taking into account Von Karman-Donnell nonlinearity. Approximate solutions are assumed to satisfy simply supported boundary conditions and Galerkin method is used to derive the closed-form expression of nonlinear load-deflection relation from which buckling loads and postbuckling paths are determined. Numerical examples are carried out and interesting remarks are given.